2021
DOI: 10.1038/s41598-021-85426-9
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin and C-reactive protein are efficient and reliable early predictors of COVID-19 associated mortality

Abstract: Since the emergence of SARS-CoV-2, numerous studies have been attempting to determine biomarkers, which could rapidly and efficiently predict COVID-19 severity, however there is lack of consensus on a specific one. This retrospective cohort study is a comprehensive analysis of the initial symptoms, comorbidities and laboratory evaluation of patients, diagnosed with COVID-19 in Huoshenshan Hospital, Wuhan, from 4th February to 12th March, 2020. Based on the data collected from 63 severely ill patients from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 66 publications
7
29
0
1
Order By: Relevance
“…Similarly, we found that a decreased lymphocyte ratio and an increased neutrophil ratio, and C-reactive protein levels correlated with disease mortality. Again, these findings are consistent with the literature, which linked these parameters to COVID-19 severity and mortality [37][38][39]. The reproducibility of these biomarker findings across several studies conducted in varying patient populations suggests that they could play a useful role in identifying an early time point for those patients with a worse prognosis who may require closer monitoring in a critical care setting.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, we found that a decreased lymphocyte ratio and an increased neutrophil ratio, and C-reactive protein levels correlated with disease mortality. Again, these findings are consistent with the literature, which linked these parameters to COVID-19 severity and mortality [37][38][39]. The reproducibility of these biomarker findings across several studies conducted in varying patient populations suggests that they could play a useful role in identifying an early time point for those patients with a worse prognosis who may require closer monitoring in a critical care setting.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, laboratory tests confirmed infection in the patient; however, lymphocytes, leukocytes, ALT and AST were found to be within the normal range. An increase in C-reactive protein was observed, which might be an adverse clinical manifestation [ 10 , 11 ]. Although the pregnant woman was diagnosed with PROM, no risk factors, including pre-eclampsia, history of cesarean section or fetal distress, were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Reservoir host animals of CoV, including rodents and bats, carry similar receptors as present in intermediate hosts including bovines, camels and masked palm civet (Salata et al 2020;Wang et al 2020;Ye et al 2020). The presence of these receptors (ACE2 or DPP4) in humans makes them susceptible to MERS-CoV and SARS-CoV, causing MERS and SARS infections, respectively (Song et al 2005;Tiwari et al 2020;Ali et al 2021). The spike present on the MERS-CoV has the capability to become accustomed to the disparity in the receptors DPP4 of the host species (Letko et al 2018).…”
Section: Transmissionmentioning
confidence: 99%
“…Though it is stated that pathogenesis of COVID-19 is not clear, however, in most of the cases, it primarily affects the lungs. Ali et al (2021) have stated in this regards that the key mechanism for SARS-CoV-2 invasion is the binding of the virus to the ACE2 membrane-bound receptor and the host cell's internalization of the complex (Zhang et al 2020). ACE2, a glycoprotein and metalloprotease, is present both in membrane-bound, as well as in soluble, forms (Jia et al 2009).…”
Section: Pathogenesis Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation